2004
DOI: 10.1074/jbc.m409703200
|View full text |Cite
|
Sign up to set email alerts
|

The Leucine-rich Repeat Protein LRIG1 Is a Negative Regulator of ErbB Family Receptor Tyrosine Kinases

Abstract: The molecular mechanisms by which mammalian receptor tyrosine kinases are negatively regulated remain largely unexplored. Previous genetic and biochemical studies indicate that Kekkon-1, a transmembrane protein containing leucine-rich repeats and an immunoglobulin-like domain in its extracellular region, acts as a feedback negative regulator of epidermal growth factor (EGF) receptor signaling in Drosophila melanogaster development. Here we tested whether the related human LRIG1 (also called Lig-1) protein can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
227
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(236 citation statements)
references
References 31 publications
7
227
1
1
Order By: Relevance
“…Other studies, though, have reported that Lrig1‐expressing stem cells are predominantly quiescent 8, 25, and that Lrig1 serves as a negative regulator of EGF receptor signaling to suppress stem cell proliferation 8, 27, 28. How, then, do we explain our finding that EGF and BPE promote proliferation, and stimulate the accumulation of Lrig1, in HMGECs?…”
Section: Discussionmentioning
confidence: 68%
“…Other studies, though, have reported that Lrig1‐expressing stem cells are predominantly quiescent 8, 25, and that Lrig1 serves as a negative regulator of EGF receptor signaling to suppress stem cell proliferation 8, 27, 28. How, then, do we explain our finding that EGF and BPE promote proliferation, and stimulate the accumulation of Lrig1, in HMGECs?…”
Section: Discussionmentioning
confidence: 68%
“…Two negative regulators of RTKs, namely Sprouty and Kekkon, which have subsequently evolved in insects, retain complex relationships with Cbl both in insects and in mammals [23][24][25][26]. In addition, the association of these inhibitors with Cbl leads to the ubiquitylation and degradation of Sprouty and LRIG in the proteasome, which subsequently limits their inhibitory capacity (see Fig.…”
Section: Regulation Of Receptor Endocytosismentioning
confidence: 99%
“…The structural similarity of LRIG1 to Kekkons predicted that LRIG1 would interact with and restrict ErbB signaling in mammals. Indeed, LRIG1 localizes to the basolateral surface of epithelial cells, the site of ErbB function, and physically interacts with all members of the ErbB family [23,25]. This recognition involves both LRIG1's and the receptor's ectodomains and it requires no stimulation by the respective ErbB ligand.…”
Section: Lrig1 As a Negative Regulator Of Mam-malian Rtksmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the subcellular localization of the LRIG proteins may be biologically important [13,14]. LRIG1, located at chromosome 3p14.3 [12], encodes a negative feedback regulator of epidermal growth factor receptor (EGFR) signaling [13] that enhances receptor ubiquitination and degradation rates and inhibits signaling [15][16][17]. EGFR is commonly expressed in meningiomas [18][19][20].…”
Section: Introductionmentioning
confidence: 99%